GLOBECOM'01. IEEE Global Telecommunications Conference (Cat. No.01CH37270)
DOI: 10.1109/glocom.2001.966332
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the Bluetooth system in fading dispersive channels and interference

Abstract: A noncoherent limiter-discriminator receiver is often considered for the Bluetooth system because of its simplicity and low cost. While its performance is more than adequate for some channels, the results are significantly degraded in either an interference-limited environment or a frequency selective channel. In this paper, we compare the performance of the traditional limiter-discriminator with integrate and dump filter to a more sophisticated Viterbi receiver. We find that the Bluetooth access code is suffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…3. For the channel modelling, the average root-mean-square (rms) of delay spread for a Bluetooth channel varies between 75 and 90 nsec for indoor and outdoor applications respectively, as authors of the work [12] reported. In the paper [11], the maximum rms delay spread for indoor and outdoors channels are also given 200 and 300 nsec respectively, by referencing some other studies.…”
Section: Wireless Channel Modelmentioning
confidence: 99%
“…3. For the channel modelling, the average root-mean-square (rms) of delay spread for a Bluetooth channel varies between 75 and 90 nsec for indoor and outdoor applications respectively, as authors of the work [12] reported. In the paper [11], the maximum rms delay spread for indoor and outdoors channels are also given 200 and 300 nsec respectively, by referencing some other studies.…”
Section: Wireless Channel Modelmentioning
confidence: 99%
“…A simple limiter-discriminator followed by integrate-anddump post-detection filtering [1], [4] is often employed in Bluetooth devices. The resulting receiver is called limiterdiscriminator with integrator (LDI) receiver.…”
Section: Introductionmentioning
confidence: 99%
“…The optimum GFSK demodulator is the trellis-based Viterbi decoder [1], [2], [3]. These designs always assume a certain nominal value for the modulation index h. However, the modulation index in Bluetooth is allowed to vary in a relatively large interval, leading to a varying trellis structure for sequence detection with possibly tremendous number of states.…”
Section: Introductionmentioning
confidence: 99%
“…It exhibited a 6 dB improvement over the LDI but relied on a known exact modulation index. Other Bluetooth receivers deployed the Viterbi algorithm to search for the minimum Euclidean distance path through the state trellis [6] [7]; such receivers exhibited a high power efficiency but experience high computational complexity. These receivers also assume a nominal value of the modulation index.…”
Section: Introductionmentioning
confidence: 99%